Social consequences and the cost of crime - M. P. Kleymenov; I. M. Kleymenov (Правоприменение)
The subject. The social consequences and the price of crime are a little-studied problem in the domestic science of criminology. Meanwhile, her research is of great theoretical and practical importance. From a theoretical point of view, it is important to identify and characterize possible types of harm in all spheres of public relations without exception. This will expand the scientific boundaries of criminology. In practical terms, a description of the economic parameters of the consequences of crime is necessary to determine the real budget of the bodies directly and indirectly involved in countering criminal activity.The purpose of the article is to outline the contours of a monographic in-depth study of the social consequences and the price of crime.Methodology. Dialectical and systematic approaches, analysis, synthesis, induction, deduction, sociological, statistical and comparative methods are used. Main results and conclusions. It is advisable to consider the social consequences of crime in two aspects: static and dynamic. They stand out statically, medical, demographic, sociopsychological, environmental, biological, cultural, legal, political and economic consequences of crime. Economic consequences have a value expression, so they are the price of crime. The dynamic aspect of the social consequences of crime is recognized through the phenomenon of criminalization of public relations, the final result of which is the total destruction of the state. It is concluded that currently the most relevant is the study of the economic consequences of crime, which is its measurable price. Artificial intelligence and Big Data should be used for this.